Design of a load elevator as a measure to reduce ergonomic risks - Sarmiento-Ortiz, Fabian (2024)
Manual handling of loads in work environments poses significant ergonomic risks, leading to musculoskeletal disorders and injuries. To address this, mechanical solutions are essential to optimize processes and ensure employees' health and well-being. In this study utilized four methodologies: the Ergonomic Checklist, NIOSH Equation, Snook and Cirello Tables, and the INSHT Technical Guide. These tools evaluated the physical load and risks of manual lifting. Concurrently, a load lifter was developed, utilizing a tractor system powered by an electric motor and a chain hoist, all automated by a PLC. The evaluations highlighted the high risks of manual load handling. After implementation it reduced unacceptable risk to acceptable as well as the distance workers needed to manually move loads was reduced from 8 meters to 2 meters with the automatic lift, a 75% decrease and increasing process efficiency. The designed hoist has a 500 kg capacity, streamlining the product reception and storage process. The introduction of the freight elevator, as an ergonomic solution, is pivotal in reducing workplace risks and enhancing safety and efficiency. This research underscores the need to embrace advanced technologies to tackle ergonomic issues in work settings.